2013
DOI: 10.1111/jfpp.12147
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Stability and Quality Characteristics of Muskmelon Ready to Serve Beverage Formulations as Influenced by Hydrocolloids

Abstract: Muskmelon (Cucumis Melo.L.) is a tropical fruit with an exotic flavor and color. The fruit is mostly consumed as fresh and seldom processed. Muskmelon pulp is a good source of carotenoids (1,732 μg/100 g) with low sugar content which was used for the development of beverage formulations. Cloud stability of the muskmelon beverage formulations using hydrocolloids such as guar gum, gum tragacanth, pectin and sodium alginate were investigated. Addition of a combination of sodium alginate and pectin in the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In this context, some experiments concerning the addition of several hydrocolloids, for instance pectin (E440), carboxymethyl cellulose (CMC) (E446), gellan (E418) and xanthan gum (E415), to special fruit and vegetable juices as well as beverages containing fruit and vegetable juice and other products were made (Aghajanzadeh, Ziaiifar, & Kashaninejad, 2016;Babbar, Aggarwal, & Oberoi, 2015;Gaspar, Laureano, & Sousa, 1998;Genovese & Lozano, 2001;Ibrahim et al, 2011;Liang et al, 2006;Mattes & Endress, 2000;Niederauer, 2000;Okoth, Kaahwa, & Imungi, 2000;Paquet et al, 2014;Sallaram, Pasupuleti, Durgalla, & Kulkarni, 2014;Will, Hagemann, Dietrich, & Zimmer, 1999;Yin, Liu, Dai, Zhang, & Lei, 2015). It is shown that by means of the addition of hydrocolloids (usually 0.1%-3.0%) cloud stability can be improved sufficiently in beverages (Genovese & Lozano, 2001;Liang et al, 2006).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…In this context, some experiments concerning the addition of several hydrocolloids, for instance pectin (E440), carboxymethyl cellulose (CMC) (E446), gellan (E418) and xanthan gum (E415), to special fruit and vegetable juices as well as beverages containing fruit and vegetable juice and other products were made (Aghajanzadeh, Ziaiifar, & Kashaninejad, 2016;Babbar, Aggarwal, & Oberoi, 2015;Gaspar, Laureano, & Sousa, 1998;Genovese & Lozano, 2001;Ibrahim et al, 2011;Liang et al, 2006;Mattes & Endress, 2000;Niederauer, 2000;Okoth, Kaahwa, & Imungi, 2000;Paquet et al, 2014;Sallaram, Pasupuleti, Durgalla, & Kulkarni, 2014;Will, Hagemann, Dietrich, & Zimmer, 1999;Yin, Liu, Dai, Zhang, & Lei, 2015). It is shown that by means of the addition of hydrocolloids (usually 0.1%-3.0%) cloud stability can be improved sufficiently in beverages (Genovese & Lozano, 2001;Liang et al, 2006).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…The protective colloid has an affinity for the continuous phase and thereby connects the two phases and stabilizes the suspension (Glicksman, 1982a; Tadros, 2013). Addition of a combination of sodium alginate and pectin in the ratio of 1:1 with a concentration of 0.25% of beverage resulted in cloud stabilization of muskmelon beverage with high overall acceptability was studied by Sallaram, Pasupuleti, Durgalla, and Kulkarni (2014). Taiwo and Gift (2013) used carboxymethylcellulose and xanthan gum in ratio 2:1 for cloud stabilization in tomato‐carrot juice blends.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal formulation showed good stability and physical properties, sensory analysis, particle size distribution, and rheological properties GG stabilized muskmelon juice Sallaram et al (2014) Fermented milk beverages (FMB) The quality of GG-based FMBs preserved and replaced the fat in the formulation…”
Section: Referencesmentioning
confidence: 99%